Clinical Profile of Child and Adolescent (≤16 years) Psychotic Disorders at a Tertiary Care Centre In India - Sagar, Rajesh; Pattanayak, Raman Deep; Mehta, Manju (Journal of Basic & Applied Sciences, 2012)
Background: Over past two decades, there is an increasing recognition that the psychotic disorders can begin in children at a very young age.Only a few prior studies from India have explored the clinical profile of non-affective psychotic disorders at a younger age. Aims:The study aims to describe the clinical profile of child and adolescent (≤16 years) psychotic disorders. Methods:The study was conducted as a three-year descriptive, retrospective review. All the patients aged ≤16 years, with a diagnosis of Schizophrenia and other psychotic disorders as per Diagnostic and Statistical Manual, 4th edition Text Revision (DSM-IV TR) criteria who presented to the weekly child and adolescent psychiatry clinic at All India Institute of Medical Sciences, New Delhi were included. Relevant information was retrieved on a semi-structured datasheet. Results:The clinic prevalence for schizophrenia and other psychotic disorders was found to be 2.47% (40/1618), of which five patient records were either unavailable or inadequate for inclusion. The mean age was 13.97(±1.46) years with an equal representation of males and females. A very early-onset (≤12 years) was present in 48.3% of the sample. Median duration of psychotic illness was 12 months (0.1-48 months) and majority (94.3%) had a continuous course. Family history was positive for psychiatric illness in 22.9%, while an identifiable psychosocial stressor was temporally related in 17.1% of sample. A comorbid psychiatric disorder was present in 14.5%, commonest being subnormal intellectual functioning. Auditory hallucinations appeared to be a common (51.5%) symptom, however these were evident primarily from patient’s behavior rather than self-report in over half of them. Visual hallucinations with ghost or animal theme were present in 17.1% and delusions were manifested by 40% of sample. Disorganized speech and catatonia were less frequent. Nearly 17.1% of sample left school after onset of psychosis and all patients showed some disruption in social, inter-personal and academic functioning. Conclusion: The present study adds to the limited literature on clinical presentation and phenomenology of early-onset psychotic disorders in Indian population.